2021
DOI: 10.1186/s12915-021-01052-x
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale genomic analysis reveals the genetic cost of chicken domestication

Abstract: Background Species domestication is generally characterized by the exploitation of high-impact mutations through processes that involve complex shifting demographics of domesticated species. These include not only inbreeding and artificial selection that may lead to the emergence of evolutionary bottlenecks, but also post-divergence gene flow and introgression. Although domestication potentially affects the occurrence of both desired and undesired mutations, the way wild relatives of domesticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 83 publications
3
17
0
Order By: Relevance
“…SAMM had a highest linkage disequilibrium level, followed by Chinese Merino and Australian Merino (Figure S1). These results were consistent with the observations in other domestic animals including dogs (Gou et al, 2015), pigs (Muñoz et al, 2019), chickens (Wang et al, 2021;Xu et al, 2021), and ducks (Guo et al, 2021), indicating that domestication and artificial selection induced a loss of genetic diversity and an increase of inbreeding.…”
Section: Introductionsupporting
confidence: 90%
“…SAMM had a highest linkage disequilibrium level, followed by Chinese Merino and Australian Merino (Figure S1). These results were consistent with the observations in other domestic animals including dogs (Gou et al, 2015), pigs (Muñoz et al, 2019), chickens (Wang et al, 2021;Xu et al, 2021), and ducks (Guo et al, 2021), indicating that domestication and artificial selection induced a loss of genetic diversity and an increase of inbreeding.…”
Section: Introductionsupporting
confidence: 90%
“…Studies also showed that linked selection and population structure could bias Sequentially Markovian Coalescent model inferences (Johri et al, 2021; Mazet et al, 2016). In addition, psmc might misestimate splitting times between domestical species and their wild relatives because this model does not take into account the possible effect of admixture (Wang et al, 2021). However, few studies have examined whether recent fluctuations in population size (<1,000 years ago) may influence psmc inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have applied psmc to investigate the population history of extinct or endangered species (Hu et al, 2020; Hung et al, 2014; Saremi et al, 2019), date the divergence time between sister species (Westbuty et al, 2019), and examine interactions between historical climate fluctuations and population changes (Mays et al, 2018; Nadachowska‐Brzyska et al, 2015). psmc has also been used to infer the demographic history of domesticated species and estimate when the domesticated species (or their progenitors) split from their wild relatives (Wang et al, 2021). Despite the popularity and reliability of psmc for tracing demographic history back to hundreds of thousands of years ago, few studies have explored how recent population changes (e.g., recent population bottlenecks) may affect psmc inferences.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a parallel allele frequency pattern, based on synonymous and missense variants, was obtained that was consistent with observed patterns in humans and cattle [ 47 , 48 ]. Wang et al defined high-impact SNPs as having a PROVEAN score < −2.5 for missense variants [ 12 ]. Herein, we focused on frequency changes between the two chicken lines and conservation status, to evaluate chicken phenotype high-impact variants rather than on PROVEAN score for missense SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, comparison of the original line and the selected line is an excellent means by which to dissect genetic architecture and explore the genes affecting BrW. Wang et al revealed a new landscape of genomic changes associated with domestication by investigating the high-impact (missense) single nucleotide polymorphisms (SNPs), which were determined by low PROVEAN score [ 12 ]. Thus, it is conducive to identify the genes that respond to artificial selection by studying the missense SNPs in JX chicken.…”
Section: Introductionmentioning
confidence: 99%